Tapering-free monocrystalline Ge nanowires synthesized via plasma-assisted VLS using In and Sn catalysts. (1st October 2022) - Tang, Jian; Wang, Jun; Maurice, Jean-Luc; Chen, Wanghua; Foldyna, Martin; Yu, Linwei; Leshchenko, Egor D; Dubrovskii, Vladimir G; Cabarrocas, Pere Roca I
Abstract: In and Sn are the type of catalysts which do not introduce deep level electrical defects within the bandgap of germanium (Ge). However, Ge nanowires produced using these catalysts usually have a large diameter, a tapered morphology, and mixed crystalline and amorphous phases. In this study, we show that plasma-assisted vapor–liquid–solid (PA-VLS) method can be used to synthesize Ge nanowires. Moreover, at certain parameter domains, the sidewall deposition issues of this synthesis method can be avoided and long, thin tapering-free monocrystalline Ge nanowires can be obtained with In and Sn catalysts. We find two quite different parameter domains where Ge nanowire growth can occur via PA-VLS using In and Sn catalysts: (i) a low temperature-low pressure domain, below ∼235 °C at a GeH4 partial pressure of ∼6 mTorr, where supersaturation in the catalyst occurs thanks to the low solubility of Ge in the catalysts, and (ii) a high temperature-high pressure domain, at ∼400 °C and a GeH4 partial pressure above ∼20 mTorr, where supersaturation occurs thanks to the high GeH4 concentration. While growth at 235 °C results in tapered short wires, operating at 400 °C enables cylindrical nanowire growth. With the increase of growth temperature, the crystalline structure of the nanowires changes from multi-crystalline to mono-crystalline and their growth rate increases from ∼0.3 nm s −1 to 5 nm s −1 . The cylindrical Ge nanowires grown at 400°C usually have a length of few microns and a radius of around 10 nm, which is well below the Bohr exciton radius in bulk Ge (24.3 nm). To explain the growth mechanism, a detailed growth model based on the key chemical reactions is provided.